A study on the effect of tourist perceptions on postconsumer behaviors (Revista "Boletín el Conuco", 2022)
Objective: To establish the association between the perceptions of tourists visiting Villavicencio and Hacienda CSQ'No with their post-consumption intentions. Method: A literature review was conducted for the different approaches to quality and perceived value, recommendation and repurchase intentions, and the scales developed for their measurement. An applied research exercise was proposed, circumscribed to the perceptions of tourists who visited Hacienda CSQ'No on their behavioral intentions, by means of surveys. The methodology used was quantitative, with a non-probabilistic convenience sample. Results: It was confirmed that there is a positive and significant correlation between quality and perceived value with the intention to repurchase and recommendation. Also, a behavioral difference was observed between the groups visiting the destination. Discussion: The findings contribute to a better understanding of the post-consumer behavioral perceptions and attitudes of tourists visiting the destination, taking into account the moderating effect of travel group. Conclusions: Knowledge of the behavioral attitudes of groups, can contribute to the overall development and improvement of the competitive advantage of the destination.
Keywords: perception; recommendation intent; repurchase intent; tourist